Role of LncRNAs and CircRNAs in Bone Metabolism and Osteoporosis - Patil, Suryaji; Dang, Kai; Zhao, Xin; Gao, Yongguang; Qian, Airong (Frontiers in Genetics, 2020)
Bone is a mechanosensitive organ that provides strength and support. Many bone cells, various pathways, and signaling molecules coordinate the bone metabolism and also determine the course of bone diseases such as osteoporosis, osteonecrosis, osteopenia, etc. Osteoporosis is caused by increased bone resorption and reduced bone formation due to the changes in the level of different proteins and RNAs in osteoclast or/and osteoblasts. The available therapeutic interventions can significantly reduce bone resorption or enhance bone formation, but their prolonged use has deleterious side-effects. Therefore, the use of noncoding RNAs as therapeutics has emerged as an interesting field of research. Despite the advancements in the molecular field not much is known about the role of long noncoding RNAs and circular RNAs in bone homeostasis and osteoporosis. Therefore, in this article, we summarize the role of long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) in different bone cells and osteoporosis. So that it might help in the development of osteoporotic therapeutics.